'Firecracker Red' Caladium - a University of Florida Cultivar for Sunny Landscapes and Large Containers - Zhanao Deng; Brent K. Harbaugh (EDIS)
ENH 1040, a 6-page illustrated fact sheet by Zhanao Deng and Brent K. Harbaugh, introduces tuber producers to this new red fancy-leafed caladium cultivar which produces large leaves with intense red color and performs well in sunny landscapes and large containers. Published by the UF Department of Environmental Horticulture, October 2006.